SOLIDARITY BUYING AS THE SOLUTION OF COMMUNITY DEVELOPMENT IN NEW NORMAL ERA - Rahmayati Rahmayati (Proceeding International Seminar of Islamic Studies, 2021)
This research problem study discusses the impact of COVID-19 globally on economic activity, namely the level of consumption that occurs in an undesirable situation due to the impact of the fear of lack of equipment and equipment during the COVID-19 period. Apart from influencing production, consumption also influences. Namely, the emergence of a phenomenon called panic buying through the minds of some people is getting less controlled due to more fear. This research discusses the presence of solidarity buying as a solution to helping each other by continuing to carry out economic activities from the closest scope and can be carried out alternately and then distributed to parties who have an impact on their lives due to COVID-19. This research aims at community empowerment by helping each other in the surrounding environment, but economic turnover can run through silodarity buying which is not only individual but more concerned with social life amid the conditions of COVID-19. By using research that is a qualitative approach with several methods so that it can help the process to achieve a desired result. For the first to use development research (Development Research). Research and development is a process to develop a new product or improve an existing product, which can be justified. The results of the study show that solidarity buying can maintain the unfinished economic chain during the COVID-19 period through tolerance in purchasing goods or food from small and medium enterprises. The conclusion from the research is that the new normal period requires increased tolerance between humans as an economic continuity of life by not doing panic buying and continuing to run the small and medium economy by buying existing products as needed.Keywords: Solidarity Buying, Development, New Normal Era.____________________________________________________